USE OF FRUIT CHLOROFORM PARTISI PARE THE WHITE RAT HYPERGLYCEMIC - Pakpahan, Yoana Pratiwi Clara; Suartha, I Nyoman; Anthara, Made Suma; Sudimartini, Luh Made; Dharmayudha, Anak Agung Gde Oka (Buletin Veteriner Udayana, 2017)
This study aimed to determine the efficacy of administration chloroform extract of bitter melon fruit partition to decrease blood glucose levels of hyperglycemic rat ( Rattus norvegicus ). Measurement of blood glucose levels was done before and streptozotocin injected on days -1, 0, 4, 11, and 18 after mice hyperglycemia. Treatment of bitter melon extract and chloroform partition performed after mice hyperglycemia until day 18th. This study consisted of four treatments and five repetitions using a completely randomized design. Four of this treatment is the control of rats (P0), streptozotocin-treated rat with a dose of 40 mg kg (P1), streptozotocin-treated rat with a dose of 40 mg/kg and bitter melon extract 2% (200 mg/kg) (P2) and streptozotocin-treated rat at a dose of 40mg/kg and chloroform partition 50 mg/kg (P3). The results showed that administration of chloroform partition and bitter melon fruit extract significantly ( P <0.05) to decrease the body's blood glucose levels.
Keywords: Hiperglikemia; Momordica charantia; Rattus norvegicus